The effect of obesity on periodontitis progression: the 10-year retrospective cohort study - Charupinijkul A. (2023)
Objective: Due to inconsistent findings in limited previous cohort studies, the aim of this study was to estimate the obesity effect on periodontitis progression in Thai adults. Materials and methods: This 10-year retrospective cohort study comprised 2216 employees of the Electric Generation Authority of Thailand (EGAT). Their demographic, medical, and periodontal status was collected. Subjects with periodontitis progression were defined as having ≥ 2 teeth with progression. Additional proximal clinical attachment loss ≥ 3 mm or tooth loss with severe periodontitis at baseline were used to identify disease progression at the tooth level. Central obesity was classified using the waist-hip ratio. Multi-level Poisson regression was used to determine the effect of obesity on periodontitis progression by adjusting for age, sex, education, income, smoking, alcohol drinking, exercise, diabetes mellitus, and hypertension. Results: The cumulative incidence of periodontitis progression during the 10-year period was 59.6 cases per 100 persons (95% CI: 57.5, 61.6). The univariate analysis indicated that obese subjects had 15% higher risk of progression than that of healthy subjects. However, when confounders were analyzed simultaneously, the effect of obesity was not significant with a risk ratio of 0.98 (95% CI: 0.88, 1.08). Conclusions: Despite the higher incidence of disease progression in the obese, obesity is not an independent risk factor for periodontitis progression. Clinical relevance: Obesity and periodontitis progression share many common risk factors. Using the obesity as a preliminary screening for periodontitis progression may be an alternative prevention protocol.